THE INFLUENCE OF THE 7P MARKETING MIX ON THE SUSTAINABILITY OF THE ISTANA KUNING COFFEE FESTIVAL IN PANGKALANBUN CITY - Malik, Amalia; Puspita, Helda Jaya; Firmansyah, Akbar Maulana (GEMAH RIPAH: Jurnal Bisnis, 2025)
The Istana Kuning Coffee Festival is one of the promotional strategies for local Liberica coffee from Pangkalanbun City, Central Kalimantan. This research aims to analyze the sustainability of the festival through a SWOT approach based on visitor perceptions. The analysis results show that the main strengths of the festival lie in the quality and uniqueness of Liberica coffee (score 4.15), as well as the well-regarded human resources and physical evidence aspects of the festival. However, weaknesses were found in the promotion and distribution aspects of the location (score 3.80). The greatest opportunity lies in utilizing digital promotion and collaborating with the creative industry, while the main threat comes from dependence on government budgets and post-pandemic uncertainty (score 3.50). Future development strategies need to focus on increasing promotion, diversifying funding sources, and strengthening multi-stakeholder cooperation. This result provides a basis for formulating festival sustainability policies based on local potential and marketing innovation.